The Utilization of Sulfuric Acid Waste to Filter Drugs Contained in Food - Ni Putu Ayu Ratna Dewi (Jurnal KESANS : Kesehatan dan Sains, 2022)
Abstract Introduction: Drug trafficking remains a rampant case in Indonesia. Despite measures implemented by policymakers and law enforcers, the deterrence level by traffickers to commit this crime stay low. The rising number of drug users proves the high number of drug-related crimes. Objective: To detect drug smuggled in food. Method: This research is experimental research using optimization test to determine the composition between H2SO4 and HCOH find the perfect ratio for detecting drugs. Results and Discussion: This research output is a screening test tool to detect samples suspected of containing drugs. With the development of drug detection tools, it is hoped that it can help the government and other agencies to expose drug abuse in society. Conclusion: This drug detection is an innovation in terms of preventive efforts for the community in drug eradication. The advantage of this innovation is a simple tool that the wider community can use as an initial detection or screening test